Ecological energetics of forage fish from the Mediterranean Sea: Seasonal dynamics and interspecific differences. (June 2017) - Albo-Puigserver, M.; Muñoz, A.; Navarro, J.; Coll, M.; Pethybridge, H.; Sánchez, S.; Palomera, I.
Abstract: Small and medium pelagic fishes play a central role in marine food webs by transferring energy from plankton to top predators. In this study, direct calorimetry was used to analyze the energy density of seven pelagic species collected over four seasons from the western Mediterranean Sea: anchovy Engraulis encrasicolus, sardine Sardina pilchardus, round sardinella Sardinella aurita, horse mackerels Trachurus trachurus and T. mediterraneus, and mackerels Scomber scombrus and S. colias . Inter-specific differences in energy density were linked to spawning period, energy allocation strategies for reproduction and growth, and feeding ecologies. Energy density of each species varied over time, with the exception of S. colias, likely due to its high energetic requirements related to migration throughout the year. In general, higher energy density was observed in spring for all species, regardless of their breeding strategy, probably as a consequence of the late-winter phytoplankton bloom. These results provide new insights into the temporal availability of energy in the pelagic ecosystem of the Mediterranean Sea, which are pivotal for understanding how the population dynamics of small and medium pelagic fishes and their predators may respond to environmental changes and fishing impacts. In addition, the differences found in energy density between species highlighted the importance of using species specific energy-values in ecosystem assessment tools such as bioenergetic and food web models.